2013
DOI: 10.5897/ajb2013.12814
|View full text |Cite
|
Sign up to set email alerts
|

Population structure of Gibberella xylarioides Heim and Saccas in Ethiopian forest coffee (Coffea arabica L.) systems

Abstract: Coffee wilt caused by Gibberella xylarioides (Fusarium xylarioides) is a troublesome soil borne disease of Arabica coffee (Coffea arabica L.) in Ethiopia. It has been known to be prevalent and severe in plantation, garden and semi-forest coffee production systems in that order of importance. A number of recent reports have also indicated that the disease is equally damaging coffee trees with varying intensities thereby endangering the conservation of wild coffee genetic resources in forest coffee systems of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 16 publications
0
7
0
Order By: Relevance
“…As host-pathogen interaction results reported by Sihen et al, (2013) the accession versus isolate interactions demonstrated differential effects, and thus, seedlings of Harenna accessions (P4, P6 and P11) were horizontally resistant (< 30%) to almost all isolates of G. xylarioides but susceptible to the isolate originated from the same site (H11) which induced 90% seedling death. In contrast, Yayu accessions (P47, P49 and P59) were highly resistant only to Berhane-Kontir isolate (SH21) without expressing any wilt symptoms (0.0%); although, they are susceptible to the other four isolates, namely, 'B23', 'Y21', and 'H11' and 'G11' with varying disease levels.…”
Section: Seedling Inoculation Tests Of Forest Coffee Accessionsmentioning
confidence: 83%
See 2 more Smart Citations
“…As host-pathogen interaction results reported by Sihen et al, (2013) the accession versus isolate interactions demonstrated differential effects, and thus, seedlings of Harenna accessions (P4, P6 and P11) were horizontally resistant (< 30%) to almost all isolates of G. xylarioides but susceptible to the isolate originated from the same site (H11) which induced 90% seedling death. In contrast, Yayu accessions (P47, P49 and P59) were highly resistant only to Berhane-Kontir isolate (SH21) without expressing any wilt symptoms (0.0%); although, they are susceptible to the other four isolates, namely, 'B23', 'Y21', and 'H11' and 'G11' with varying disease levels.…”
Section: Seedling Inoculation Tests Of Forest Coffee Accessionsmentioning
confidence: 83%
“…Results of greenhouse inoculation experiments proved that there was important diversity in coffee populations (within and among the forest sites) in reaction to G. xylarioides infection (Arega Z., 2006;Sihen et al, 2012 andSihen et al, 2013). However, there is a tendency towards occurrence of higher frequency of susceptibility reactions except in Harenna coffee populations that consistently revealed higher level of resistance in both sets of experiments, even despite the fact that relatively more CWD incidence recorded in the fields.…”
Section: Seedling Inoculation Tests Of Forest Coffee Accessionsmentioning
confidence: 89%
See 1 more Smart Citation
“…Greater host heterogeneity is thought to reduce susceptibility to CWD and restricts the rapid spread of the disease (Getachew et al, 2012(Getachew et al, , 2013Zeru et al, 2009). CWD is considered to be a minor problem in Ethiopia, and its coffee exports have yet to suffer large drops (Figure 1d).…”
Section: Coffee Wilt Disease In Ethiopiamentioning
confidence: 99%
“…However, its production is experiencing a remarkable decline due to aging plantations, the degeneration of planting materials, use of uncertified plant materials and attacks of pests and diseases (Tshilenge-Djim et al, 2004). Among these, coffee wilt disease (CWD) is one of the most important diseases dramatically limiting coffee production (Coste, 1989;Tshilenge-Djim et al, 2004;Girma et al, 2005;Sihen et al, 2012Sihen et al, , 2013. This fungal disease caused by Fusarium xylarioides Steyaert (teleomorph: Gibberella xylarioides Heim & Saccas) had devastated plantations in West Africa and also in DRC (Tshilenge-Djim et al, 2004).…”
Section: Introductionmentioning
confidence: 99%